COMPARISON OF BLADDER CANCER CELLS APOPTOSIS INDUCED BY METFORMIN, CISPLATIN, AND COMBINATION OF METFORMIN-CISPLATIN: IN VITRO STUDY - Lumbangaol, Arifai; Hakim, Lukman; Soebadi, Doddy M; Djojodimedjo, Tarmono (Indonesian Journal of Urology, 2020)
Objective: To evaluate the effect of metformin, cisplatin, and their combination on apoptosis of bladder cancer cells. Material & Methods: Urothelial cell lines 5637 were cultured until 80% confluence. Cells were exposed to metformin and cisplatin at certain doses for 24 and 48 hours. Cytotoxicity test was carried out by calculating the viability of bladder cancer cells using the MTT assay until IC50 of each drug was obtained. IC50 Metformin and Cisplatin obtained from the cytotoxicity test were used to induce apoptosis in bladder cancer cells using TUNEL assay. Additional combination doses of Metformin and cisplatin used to induce apoptosis were ¼ IC50 (metformin + cisplatin), ½ IC50 (metformin + cisplatin), and IC50 (metformin + cisplatin). Results: IC50 of metformin was 15 uM while cisplatin was 18 uM with a 48-hour exposure. There was a difference in the mean value of the apoptosis index in all treatment groups compared to control except for the group exposed to IC50 metformin and ¼ IC50 (metformin + cisplatin). Conclusion: Metformin administration solely is not able to increase bladder cancer cell apoptosis. Conversely, the administration of Cisplatin can significantly increase bladder cancer cell apoptosis. The combination of Metformin and Cisplatin can significantly increase bladder cancer cell apoptosis. The rate of apoptosis in line with an increase dose of the combination of these two drugs.